2019
DOI: 10.1111/jce.14222
|View full text |Cite
|
Sign up to set email alerts
|

A review of the epidemiology of atrial fibrillation in sub‐Saharan Africa

Abstract: This systematic review summarizes the data on the prevalence, risk factors, complications, and management of atrial fibrillation (AF) in sub‐Saharan Africa (SSA). Bibliographic databases were searched from inception to 31 May 2019, to identify all published studies providing data on AF in populations living in SSA. A total of 72 studies were included. The community‐based prevalence of AF was 4.3% and 0.7% in individuals aged ≥40 years and aged ≥70 years, respectively. The prevalence of AF ranged between 6.7% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…This systematic review has shown that about four in five of all AF are managed via rate-control strategy. These findings are similar to those of one other AF review in this region [122]. This demonstrates that evidenced-based AF rhythm-control strategies with catheter ablations which have been shown to have a survival benefit in AF patients with heart failure as in the CASTLE AF trial and others in a systematic review [127] are unlikely to become routine practice soon in this region.…”
Section: Atrial Fibrillation/atrial Fluttersupporting
confidence: 83%
See 1 more Smart Citation
“…This systematic review has shown that about four in five of all AF are managed via rate-control strategy. These findings are similar to those of one other AF review in this region [122]. This demonstrates that evidenced-based AF rhythm-control strategies with catheter ablations which have been shown to have a survival benefit in AF patients with heart failure as in the CASTLE AF trial and others in a systematic review [127] are unlikely to become routine practice soon in this region.…”
Section: Atrial Fibrillation/atrial Fluttersupporting
confidence: 83%
“…Risk factors of AF are similar in SSA compared to HIC, except the significantly higher prevalence of rheumatic heart disease in SSA (22% ) vs HIC (~2%) in AF patients observed in one large registry, as well as lower rates of ischemic heart disease in SSA (6%) vs HIC (~18%) [41], and high AF prevalence 25% in pericarditis in SSA vs 4.3% seen in pericarditis in HIC [121]. The findings of this systematic review are similar to those of prior reviews in Africa with respect to AF prevalences rates, risk factors, and co-morbidities [8,122]. Despite the relatively lower prevalence of AF in people of African descent, the presence of AF is associated with higher rates of strokes, heart failure, and mortality compared to Caucasians, and Black patients with AF are much younger than patients of other races [123].…”
Section: Atrial Fibrillation/atrial Fluttersupporting
confidence: 76%
“…AF burden is lowest in sub-Saharan Africa [ 29 ], possibly due in part to under-detection and non-recognition. However, it is associated with increased risk of stroke and heart failure [ 3 30 ] and recently, an increase in disability-adjusted life years (DALYs) from AF [ 31 ].…”
Section: Global Af Burden and Country Estimatesmentioning
confidence: 99%
“…In this issue of the Journal of Cardiovascular Electrophysiology, Dr Noubiap and Dr Nyaga present a comprehensive review on the epidemiology of AF in sub-Saharan Africa (SSA). 1 They are to be commended for raising awareness of this underserved population with unmet needs. What likely began as a systematic PRISMA based metaanalysis quickly transformed into a descriptive review once the heterogeneity of the population became apparent.…”
mentioning
confidence: 99%
“…Efforts at increasing AF awareness, ambulatory monitoring, anticoagulation, and other therapeutic interventions are growing and gaining widespread attention from both the cardiovascular and general medicine communities. In this issue of the Journal of Cardiovascular Electrophysiology , Dr Noubiap and Dr Nyaga present a comprehensive review on the epidemiology of AF in sub‐Saharan Africa (SSA) . They are to be commended for raising awareness of this underserved population with unmet needs.…”
mentioning
confidence: 99%